The uniform asymptotic behavior of solutions for 2D g-Navier-Stokes equations with nonlinear dampness and its dimensions - Xiaoxia Wang; Jinping Jiang (Electronic Research Archive, 2023)
In this paper, the uniform asymptotic behavior of solutions for 2D g-Navier-Stokes equations with nonlinear dampness is studied in unbounded domain. The uniform asymptotic properties of the process family is proved with the energy equation method and the uniform attractor is obtained. Finally, the dimension of the uniform attractor is estimated in the quasi-periodical case.